Prenatal genetic diagnosis: Fetal therapy as a possible solution to a positive test - Kiani, Aysha Karim; Paolacci, Stefano; Scanzano, Pietro; Michelini, Sandro; Capodicasa, Natale; D’Agruma, Leonardo; Notarangelo, Angelantonio; Tonini, Gerolamo; Piccinelli, Daniela; Farshid, Kalantary Rad; Petralia, Paolo; Fulcheri, Ezio; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background: Fetal abnormalities cause 20% of perinatal deaths. Advances in prenatal genetic and other types of screening offer great opportunities for identifying high risk pregnancies. Methods: Through a literature search, here we summarise what are the prenatal diagnostic technique that are being used and how those techniques may allow for prenatal interventions. Results: Next generation sequencing and non-invasive prenatal testing are fundamental for clinical diagnostics because of their sensitivity and accuracy in identifying point mutations, aneuploidies, and microdeletions, respectively. Timely identification of genetic disorders and other fetal abnormalities enables early intervention, such as in-utero gene therapy, fetal drug therapy and prenatal surgery. Conclusion: Prenatal intervention is mainly focused on conditions that may cause death or lifelong disabilities, like spina bifida, congenital diaphragm hernia and sacrococcygeal teratoma; and may be an alternative therapeutic option to termination of pregnancy. However, it is not yet widely available, due to lack of specialized centers.